2020
DOI: 10.3390/ijms21041273
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Robust Method for Subgrouping Non-NF2 Meningiomas According to Genotype and Detection of Lower Levels of M2 Macrophages in AKT1 E17K Mutated Tumours

Abstract: The majority of meningiomas are grade I, but some grade I tumours are clinically more aggressive. Recent advances in the genetic study of meningiomas has allowed investigation into the influence of genetics on the tumour microenvironment, which is important for tumorigenesis. We have established that the endpoint genotyping method Kompetitive Allele Specific PCR (KASP™) is a fast, reliable method for the screening of meningioma samples into different non-NF2 mutational groups using a standard real-time PCR ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Other mutations like TRAF7, AKT1, KLF4, SMO, and PIK3CA were more recently described ( 27 , 28 ) and may represent therapeutic targets ( 29 31 ). In one particular study, grade I meningiomas harboring AKT1 mutations had predominantly M2-subtype infiltrating macrophages, indicating a locally immunosuppressed tumor microenvironment ( 32 ). Additionally, it has been found that tumors initially diagnosed as WHO grade II meningiomas commonly have loss of NF2 with alterations in SMARCB1 and have an increased H3K27 methylation ( 33 ).…”
Section: Genetic Alterations Of Meningiomasmentioning
confidence: 99%
“…Other mutations like TRAF7, AKT1, KLF4, SMO, and PIK3CA were more recently described ( 27 , 28 ) and may represent therapeutic targets ( 29 31 ). In one particular study, grade I meningiomas harboring AKT1 mutations had predominantly M2-subtype infiltrating macrophages, indicating a locally immunosuppressed tumor microenvironment ( 32 ). Additionally, it has been found that tumors initially diagnosed as WHO grade II meningiomas commonly have loss of NF2 with alterations in SMARCB1 and have an increased H3K27 methylation ( 33 ).…”
Section: Genetic Alterations Of Meningiomasmentioning
confidence: 99%
“…Meningioma specimens were collected during planned tumour resections; these are surplus samples destined for the incinerator following histological analysis for diagnosis and processed using techniques previously described [ 33 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tumours were then minced into small pieces and disaggregated in digestion media (Dulbecco’s Modified Eagle Medium, DMEM supplemented with 10% FBS, 100 U/mL Penicillin, 100 U/mL Streptomycin and 20 units/mL of Type III collagenase (Worthington Biochemical Corp, Lakewood Township, NJ, USA)) overnight at 37 °C. Following digestion, the cells were pelleted at 1500 rpm for 5 min, the supernatant was removed and the pellet re-suspended in the complete medium and seeded in the appropriate tissue culture dish [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations